The Classification of Clinicians’ Information Needs While Using a Clinical Information System - Allen, Mureen (American Medical Informatics Association, 2003)
INTRODUCTION: Information needs are prevalent in clinical practice. They represent a potential source of medical errors. This study seeks to empirically determine the information needs of clinicians while using a clinical information system (CIS), and characterize those needs. In addition this paper will provide the framework necessary for the development of the solutions to these information needs. METHODS: Clinicians were observed while using a CIS. They were recorded on audiotape and the computer screen recorded on videotape. The types of question during these interactions were recorded. A classification of the questions provided the conceptual and architectural basis for the development of context-sensitive links to information resources, called infobuttons. RESULTS: There were 154 information needs. The questions were grouped into seven categories. Within these categories we were able to identify eleven specific repeated question patterns, accounting for 72 or 47% of users’ questions. DISCUSSION: These findings are applicable to a number of settings and can be generalized to other institutions. The proposed infobuttons based on six categories, will be navigational (‘how-to...’ links), cross-reference (‘what is the…’ links), domain knowledge buttons in the areas of laboratory, pharmacy, diagnosis, and definitions/general information. Using these groups we were able to identify eleven patterns of questions.